Pengukuran dan Analisis Kapasitas Infiltrasi Lahan Pada Berbagai Posisi di Kampus Unima - Medellu, Christophil S; Silangen, patricia M; palandi, windy ariastuti (Universitas Negeri Manado, 2020)
Ground water has a very close relationship, when in rainwater reaches the surface of the earth, some will enter the ground (infiltration) to be come part of ground water (groundwater) while absorbed by the ground will be come a surface run off (run off). Unima campus area has 270 hectare of land, the exictence of flat to steep topography, various vegetation and land management for campus buildings on unima very much allows different infiltrasions in various locations. This study aims to analyze the infiltration capacity of four fields and compare the infiltration capacity of the four fields using exploratory methods (eksploratory research) this research is also referred to as a very basic eksploratorion study, measurements are carried out using the horton formula and processed in microsoft excel applications. The results showed that the four lands with a lot infiltration capacity of 16,8 cm/hour with medium classifiction. Sloping land less trees infiltration capacity 34,8 cm/hour with a rather fast classification. Flat land many trees infiltration capacity of 14,4 cm/hour the clasification is rather slow. Flat land less trees infiltration capacity is rather slow. Flat land less trees infiltration capacity is 8,4 cm/hour slow classification. Of the four lands can be compared to land that has high infiltration found in sloping locations with less trees and the lowest infiltration on flat land with less trees.